Transthoracic echocardiographic assessment of cardiac output in mechanically ventilated critically ill patients by intensive care unit physicians - Bergamaschi,Valentina (2019)
Abstract Background and objectives: Transthoracic echocardiography may potentially be useful to obtain a prompt, accurate and non-invasive estimation of cardiac output. We evaluated whether non-cardiologist intensivists may obtain accurate and reproducible cardiac output determination in hemodynamically unstable mechanically ventilated patients. Methods: We studied 25 hemodynamically unstable mechanically ventilated intensive care unit patients with a pulmonary artery catheter in place. Cardiac output was calculated using the pulsed Doppler transthoracic echocardiography technique applied to the left ventricular outflow tract in apical 5 chamber view by two intensive care unit physicians who had received a basic Transthoracic Echocardiography training plus a specific training focused on Doppler, left ventricular outflow tract and velocity-time integral determination. Results: Cardiac output assessment by transthoracic echocardiography was feasible in 20 out of 25 enrolled patients (80%) and showed an excellent inter-operator reproducibility (Pearson correlation test r = 0.987; Cohen's K = 0.840). Overall, the mean bias was 0.03 L.min-1, with limits of agreement -0.52 and +0.57 L.min-1. The concordance correlation coefficient (ρc) was 0.986 (95% IC 0.966-0.995) and 0.995 (95% IC 0.986-0.998) for physician 1 and 2, respectively. The value of accuracy (Cb) of COTTE measurement was 0.999 for both observers. The value of precision (ρ) of COTTE measurement was 0.986 and 0.995 for observer 1 and 2, respectively. Conclusions: A specific training focused on Doppler and VTI determination added to the standard basic transthoracic echocardiography training allowed non-cardiologist intensive care unit physicians to achieve a quick, reproducible and accurate snapshot cardiac output assessment in the majority of mechanically ventilated intensive care unit patients.